Development of an Android-Based Franchise System in an Effort to Optimize Sales Results for Broiler Small and Medium Enterprises (UKM) during the Covid-19 Pandemic - Nasruddin Nasruddin; Rizka Awaluddin (STKIP Taman Siswa Bima, 2023)
The Covid-19 pandemic that hit Indonesia in early 2020 was the most challenging time for small and medium enterprises (SMEs). One of the UKM that was very affected during the pandemic was the broiler chicken UKM. The government has made various efforts to help UKM players during the pandemic, such as providing incentives. Business actors are not equipped with increased skills. One effort that can be made is to implement an Android-based Franchise system. This research is a Research and Development (R&D) study with an adaptation of the ADDIE model with stages; Analysis, Design, Development, Implementation, and Evaluation. Several aspects tested during the implementation process include; Functionality, Reliability, Compatibility, and Playability. The variable that becomes the evaluation aspect is whether or not there has been an increase in product sales for broiler chicken SMEs after implementing the Android-based Franchise system. From the data obtained by the researcher after using the android-based Franchise system application on broiler chicken businesses owned by 3 MSMEs sampled in the first phase of the trial, the results obtained were an increase in sales quantity.